Learning by watching: what we can learn from the Inuit’s design learning - Reitan, Janne Beate (ABM-media AS, 2013)
In this paper , I explore a single case of vernacular clothing design — the learning and practice of design for contemporary Iñupiaq - Inuit clothing made by the women of Kaktovik, North Alaska — and I hope to contribute to a better understanding of design practice and learning in general. Design research has many unexplored areas and one of these omissions is vernacular design — or ‘folk’ design. In my opinion, professional and academic design may well have something to learn from vernacular design, although this research is about vernacular learning , didactics about what, why and how to learn within the ‘making discipline’ of clothing design. The study was based on observations, interviews with seamstresses and authorial participation in designing and sewing in conformity with Iñupiaq tradition, and everything was recorded on digital video film. This investigation of Inuit clothing design indicates that learning - by - watching is the most common way of learning. Learning - by - watching is important within learning - by - doing. This concept of learning - by - watching can be seen as a development of both Schön and Wenger’s theories of learning, a concept that will probably be of great importance in further research on the learning process of design , from kindergarten to PhD . DRS // CUMULUS 2013 2nd International Conference for Design Education Researchers Oslo, 14 – 17 May 2013 Copyright © 2013. Copyright in each paper on this conference proceedings is the property of the author(s).